2019
DOI: 10.1016/j.neo.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Interferons Transcriptionally Up-Regulate MLKL Expression in Cancer Cells

Abstract: Interferons (IFNs) are key players in the tumor immune response and act by inducing the expression of IFN-stimulated genes (ISGs). Here, we identify the mixed-lineage kinase domain-like pseudokinase (MLKL) as an ISG in various cancer cell lines. Both type I and type II IFNs increase the expression of MLKL indicating that MLKL up-regulation is a general feature of IFN signaling. IFNγ up-regulates mRNA as well as protein levels of MLKL demonstrating that IFNγ transcriptionally regulates MLKL. This notion is furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 44 publications
2
48
0
5
Order By: Relevance
“…Recent literature reported that the transcription upregulation of RIPK3 and MLKL were controlled by SP1, STAT1, or CDK9 in various cancer cell lines [60][61][62] and during hepatitis. 63 JAK/STAT signaling pathway has been shown to play dynamic and important roles during muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature reported that the transcription upregulation of RIPK3 and MLKL were controlled by SP1, STAT1, or CDK9 in various cancer cell lines [60][61][62] and during hepatitis. 63 JAK/STAT signaling pathway has been shown to play dynamic and important roles during muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, RIP1/3 can also facilitate inflammasome activation, enabling the stimulation of IL1β and IL18 cytokines [168]. Moreover, there is accumulating evidence that inflammation itself can also regulate necroptosis via cytokines like type I/II IFNs, that can increase the expression of MLKL, which indicates a putative existence of a necroptosis-inflammation auto-fueling loop [169]. However, despite a clear pro-inflammatory phenotype, final immunological outcome of necroptosis may not always be sufficiently immunogenic [158].…”
Section: Necroptosis-driven Modulation Of Immune Responsesmentioning
confidence: 99%
“…Closer analysis of the genes ascribed to cell death pathways revealed a trend in which the ∆ ist/∆nsm showed slightly higher expression compared to the single ∆ nsm or ∆ ist deletion, suggestive that the parasite requires both effectors to efficiently inhibit the transcription of genes involved in cell death ( Figure 4C). PKR (aka EIF2AK2) and MLKL are known direct targets for interferon induced transcription and are key components in the JAK1/STAT1 signaling cascade responsible for execution of interferon driven necroptosis upon Caspase 8 inhibition (Knuth et al, 2019;Kuhen and Samuel, 1997;Sarhan et al, 2019;Thapa et al, 2013). Given the known ability of T. gondii to block Caspase 8 activity (Payne et al, 2003;Vutova et al, 2007), and the critical roles of PKR and MLKL in necroptosis (Sun et al, 2012;Thapa et al, 2013) we decided to further focus on these two genes.…”
Section: Tgnsm Together With Tgist Inhibit Ifn-γ Induced Necroptoticmentioning
confidence: 99%